Evaluation of immunogenicity and safety of VARIVAX™ New Seed Process (NSP) in children - Shelly D. Senders; Nickoya D. Bundick; Jianing Li; Carol Zecca; Frans A. Helmond (Taylor & Francis Group, 2018)
Prior to availability of an effective vaccine, an estimated 4 million cases of varicella occurred annually in the United States, resulting in 10,000 hospitalizations and over 100 deaths. With the increased usage of a two-dose varicella vaccine (as recommended by the ACIP), approval of other VZV-containing products and the adoption of varicella vaccination in additional countries, the demand for VZV-containing vaccines has increased. This study (NCT02062502) evaluated the safety, tolerability, and immunogenicity of VARIVAX™ (VAR, varicella vaccine live) manufactured using a new seed manufacturing process (VARNSP) compared to the currently licensed VAR. Healthy children 12-23 months were randomized (1:1) into Group 1 (2 doses of VARNSP given concomitantly with M-M-R™ II, ∼3 months apart) versus  Group 2 (2 doses of VAR given concomitantly with M-M-R™ II, ∼3 months apart).  Serum samples collected prior to vaccination on Day 1 and 6 weeks Postdose 1 were tested for antibody to VZV using a glycoprotein enzyme-linked immunosorbent assay (gpELISA).  Safety was assessed Days 1 to 42 following each vaccination. Six weeks Postdose 1, the response rate (percent of subjects with VZV antibody titer ≥5 gpELISA units/mL) of VARNSP was non-inferior compared to VAR.  Vaccine-related adverse events (AEs) were comparable with the exception of measles-like rash, where a greater number of rashes were observed with VAR than VARNSP.  The 2 vaccination groups were comparable with incidence rates of AEs, injection-site AEs, vaccine-related AEs, systemic AEs, and serious AEs. This new process is an important innovation for the extreme demand of sustaining sufficient supplies of varicella vaccine to protect our communities against diseases caused by VZV.